2020
DOI: 10.3390/polym12051089
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Composite Reinforced with Three-Dimensional Printed Fibers

Abstract: This study used melt-electrospinning writing to fabricate three-dimensional fiber constructs by embedding them in a polyvinyl alcohol (PVA) matrix to obtain thin composite films. Fourier transform infrared spectroscopy (FTIR) and dynamic scanning calorimetry (DSC) were used to demonstrate an interaction between the polycaprolactone (PCL) fibrous phase and the PVA matrix phase. Following this, the mechanical deformation behavior of the composite was investigated, and the effect of reinforcement with three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Nevertheless, they displayed substantial enhancement of specific tensile strength in comparison to the PVA TF and PVA SPTF-RO samples. The calculated value of specific tensile strength of the PVA SPTF is found to be comparable (same order of magnitude) to the data available in the literature for different PVA composites [48,56,72,73] and other types of polymer composites [11,72,74,75]. For instance, Ding et al [72] prepared PVA hydrogels with 2 wt% of PVA, 0.4 wt% borax (PB) and cellulose nanofibers-polypyrrole (CNFs-PPy/PB) and compared it with hydrogel synthesized in the absence of polypyrrole (CNF/PB).…”
Section: Tensile Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, they displayed substantial enhancement of specific tensile strength in comparison to the PVA TF and PVA SPTF-RO samples. The calculated value of specific tensile strength of the PVA SPTF is found to be comparable (same order of magnitude) to the data available in the literature for different PVA composites [48,56,72,73] and other types of polymer composites [11,72,74,75]. For instance, Ding et al [72] prepared PVA hydrogels with 2 wt% of PVA, 0.4 wt% borax (PB) and cellulose nanofibers-polypyrrole (CNFs-PPy/PB) and compared it with hydrogel synthesized in the absence of polypyrrole (CNF/PB).…”
Section: Tensile Propertiessupporting
confidence: 79%
“…The size of the thin film is also governed by the size of the fibers or particles added to improve its mechanical properties. Therefore, helicoidally arranged polyacrylonitrile sub-microfibers were used for reinforcing PVA to improve its mechanical properties [ 48 , 56 ]. Further, polyacrylonitrile filler sub-microfibers were used for reinforcing PVA due to their high Young’s modulus (∼3.1 GPa) [ 57 ] and compatibility with PVA.…”
Section: Methodsmentioning
confidence: 99%
“…As PCL is highlighted in several reviews on clinical translation of tissue engineering products, the transition from university-led research to application in the clinic is often negatively impacted by the need to repeat experiments with medical-grade polymers. In this instance, our understand- Measured as M w = 80 kDa [31] [ 11,16,12,20,[22][23][24]26, Sigma Aldrich Product number 440744 [46] M n = 80 × 10 3 [ 5,21,56,57] M n = 35 × 10 3 M w = 83 × 10 3 [ 13] M w = 45 kDa [58][59][60] M n = 45 × 10 3 [ 61] [ 5,13,21,[56][57][58][59][60][61] Capa 6400 M w ≈ 37 × 10 3 a) MFI = 40 b) [ 62,63] Capa 6430…”
Section: Why Pcl?mentioning
confidence: 99%
“…This is one approach to shift the biofabrication window to softer hydrogels and matrices while retaining handling or biomechanical requirements. [35,38,42,57] Such composite approaches, reinforcing MEW-fabricated PCL scaffolds into hydrogels that include gelatin methacryloyl (GelMA), show promising results regarding the stiffness increasing by up to 54-fold. [42] In this fiber-reinforced composite study, embedded human chondrocytes showed good viability and retained their roundish morphology, showing compatibility in terms of stiffness and biological cues for cartilage applications.…”
Section: Soft Network Compositesmentioning
confidence: 99%
See 1 more Smart Citation